Seismic performance of a non-through-core concrete between concrete-filled steel tubular columns and reinforced concrete beams. (January 2017) - Ding, Fa-xing; Yin, Guo-an; Wang, Li-ping; Hu, Di; Chen, Gang-qiang
Abstract: This paper aims to investigate the seismic behavior of a new type of non-through-core connection between a concrete-filled steel tubular (CFST) column and steel reinforced concrete (SRC) beams. In this original connection, the U-shaped steel corbels are welded to the CFST column. A strengthening ring beam is used to enhance the stiffness of the connection. Cyclic loading tests were conducted on two beam-column connection specimens. A finite element (FE) model was then developed and validated by a comparison with the experimental results. The results of the FE analysis are in good agreement with the experimental results, which demonstrated the rationality of the proposed formula for concrete damage variable based on the elastic modulus in the FE analysis. Based on the test and numerical results, the hysteretic response, the skeleton curves, the strain, ductility, stiffness degradation and energy dissipation are discussed. It is shown that the proposed connection has a favorable seismic performance. The effect of the axial compression ratio ( n ) on the seismic behavior of the connection is also discussed through parametric studies. Highlights: A new type of non-through-core connection was proposed and tested. Precise and concise formulas were proposed to calculate the concrete damage variable. A 3D finite element model was created and validated by test results. The seismic behavior of the connection under cyclic loading was thoroughly evaluated. The proposed connection displays favorable energy dissipation capacity.